Multi-locus genome-wide association studies for root system architectural traits in Ethiopian sorghum (Sorghum bicolor L.) landraces - Mitiku, Abel Debebe; Feyissa, Tilaye; Woldetensaye, Alemu Tirfessa; Chikssa, Habte Nida; Menamo, Temesgen Matiwos; Abebe, Tewodros Mesfin; Bante, Kassahun (BioMed Central, 2025)
Background: Drought is a major constraint to sorghum production. Developing drought-tolerant sorghum varieties is crucial. Optimal root system architecture (RSA) plays a vital role in plant adaptation and productivity under water- limited environment. Genetic assessments of untapped Ethiopian core sorghum germplasm to identify quantitative trait nucleotides (QTN) for RSA traits are crucial. Therefore, this study aimed to identify genetic markers associated with seven RSA and related traits in 182 Ethiopian core sorghum-landraces using multi locus genome-wide association studies (ML-GWAS) using SNP markers.